2011
DOI: 10.1111/j.1365-2036.2011.04716.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: insulin resistance and sustained virological response in hepatitis C

Abstract: SUMMARY BackgroundA higher baseline homeostasis model assessment of insulin resistance (HOMA-IR) score has sometimes predicted a poorer sustained virological response (SVR) rate to peginterferon ⁄ ribavirin therapy in treatment-naïve chronic hepatitis C patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
2
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 37 publications
(77 reference statements)
5
65
2
1
Order By: Relevance
“…Our study shows that CH-C is independently associated with three important metabolic conditions: IR, DM and hypertension. Although the association of HCV with IR and DM has been previously reported, [18][19][20][21][22][23][24] the association of HCV with hypertension is a novel finding. 3,4 In fact, in one of our previous population-based studies, 21 we reported that the association of HCV with IR and DM might have been attenuated in the last decade by the epidemics of obesity.…”
Section: Discussionmentioning
confidence: 74%
“…Our study shows that CH-C is independently associated with three important metabolic conditions: IR, DM and hypertension. Although the association of HCV with IR and DM has been previously reported, [18][19][20][21][22][23][24] the association of HCV with hypertension is a novel finding. 3,4 In fact, in one of our previous population-based studies, 21 we reported that the association of HCV with IR and DM might have been attenuated in the last decade by the epidemics of obesity.…”
Section: Discussionmentioning
confidence: 74%
“…168 Coexistent hepatic steatosis is common in chronic hepatitis C (HCV) infection and is strongly associated with more advanced liver disease. [169][170][171] Another large study showed high prevalence of steatosis (40.5%) and steatohepatitis (15%) in patients with primary biliary cirrhosis (PBC), 172 although at least some of the steatosis and steatohepatitis in that study was suspected to be due to alcohol consumption. In clinical practice, it is not uncommon for obese and/or diabetic patients with autoimmune liver disease to exhibit steatosis and steatohepatitis in their liver biopsies.…”
Section: Bariatric Surgerymentioning
confidence: 95%
“…11 This observation with dual peginterferon/ribavirin therapy was further strengthened by two recent meta-analyses. 9,10 In the first one, 9 carried out on 17 studies, despite some heterogeneity among studies, SVR associated with peginterferon/ribavirin was significantly higher in patients with low HOMA-IR (i.e., <2) irrespective of HCV genotype (genotype 1, OR 5 2.16; genotype 2 and 3, OR 5 3.06; genotype 4, OR 5 6.65). The second metaanalysis 10 assessed 14 studies involving 2,732 patients, and concluded that HCV patients with IR have a 20% lower SVR rate than patients without IR, thereby hinting that baseline HOMA-IR index is a major determinant of SVR with peginterferon/ribavirin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In HCV-infected patients, IR appears to influence disease progression and response to treatment with peginterferon alpha and ribavirin. 9,10 IR appears to be associated with a lower rate of sustained virologic response (SVR) in patients receiving peginterferon alpha and ribavirin. In a study by Romero-Gomez et al, 11 the effect of IR on SVR was assessed in patients with HCV genotype 1 who received peginterferon alpha plus ribavirin.…”
mentioning
confidence: 99%